2020
DOI: 10.1097/psy.0000000000000851
|View full text |Cite
|
Sign up to set email alerts
|

Acute Stress Disorder Among Frontline Health Professionals During the COVID-19 Outbreak: A Structural Equation Modeling Investigation

Abstract: Objective: The outbreak of COVID-19 that commenced in December 2019 in Wuhan, China, has caused extensive public health concerns and posed substantial challenges to health professionals, especially for those in the center of the epidemic. The current study aimed to assess the prevalence, related factors, and mechanism of acute stress disorder (ASD) among health professionals in Wuhan during this critical period. Methods: The study used a cross-sectional design. Self-administered questionnaires were distributed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 36 publications
3
28
0
Order By: Relevance
“…Our findings, along with previous conclusions, indicated that acute stress response was associated with QoL. A study on front-line health professionals during the outbreak of COVID-19 showed that acute stress response led to serious emotional distress and chest pain (Wang et al, 2020). Chaudhury et al (2015) demonstrated that a history of acute stress increased individuals' susceptibility to depression by changing molecular activity in the brain.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Our findings, along with previous conclusions, indicated that acute stress response was associated with QoL. A study on front-line health professionals during the outbreak of COVID-19 showed that acute stress response led to serious emotional distress and chest pain (Wang et al, 2020). Chaudhury et al (2015) demonstrated that a history of acute stress increased individuals' susceptibility to depression by changing molecular activity in the brain.…”
Section: Discussionsupporting
confidence: 80%
“…Our findings suggested that the front-line medical staff exhibited greater levels of acute stress. Wang et al (2020) highlighted that acute stress disorder is a prominent psychological problem for front-line health professionals. Working on the front-line is an independent risk factor for negative emotions (Lai et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This study also observed a strong link between COVID-19 pandemic and emotional distress such as depressive symptoms and anxiety, acute stress disorder and psychosomatic symptoms (such as chest pain). 7 In the UK National Health Service (NHS), frontline healthcare workers are likely to be particularly vulnerable to mental health issues as a result of COVID-19 outbreak. Their work environment has changed dramatically, and they have been exposed to alarming levels of stress.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…A meta-analysis revealed that the COVID-19 pandemic increases the mental health problems of the global population, particularly health care workers (5). Some other studies conducted during the outbreak period also showed the high prevalence of mental health problems such as depression, anxiety, insomnia, and acute stress among medical staffs (6)(7)(8)(9).…”
Section: Introductionmentioning
confidence: 99%
“…Zhang's study suggests that insomnia symptoms are positively associated with low education level, currently working in an isolation unit, worried about being infected, perceiving lack of helpfulness in terms of psychological support from the news or social media concerning COVID-19, and having very strong uncertainty regarding effective disease control (7). Besides, acute stress disorder is found to be associated with psychosomatic symptoms as well as hostility (9). Furthermore, social support, coping style, and personality are also considered to play an important role in the prevalence of mental health problems.…”
Section: Introductionmentioning
confidence: 99%